Patients with head and neck cancer treated with radiotherapy: Their experiences after 6 months of prophylactic tooth extractions and temporary removable dentures. Issue 5 (23rd March 2021) - Brahm, Carl‐Otto; Borg, Carina; Malm, Dan; Fridlund, Bengt; Lewin, Freddi; Zemar, Ahmed; Nilsson, Peter; Papias, Apostolos; Henricson, Maria
Abstract: Objectives: The impact of dental occlusion on the experiences of head and neck cancer patients and their oral, social and psychological functioning has been sparsely investigated. There is a lack of knowledge regarding the experience of tooth loss and dentures among patients treated for head and neck cancer. The aim of this study was to describe the experiences of head and neck cancer patients of prophylactic tooth extractions and temporary removable dentures, 6 months after radiotherapy treatment. Material and methods: An individual interview with 25 patients 6 months after radiotherapy was subjected to a qualitative content analysis. Results: Two categories, Impaired oral function and Belief in the future, and seven subcategories described the patients' experiences of temporary removable dentures during the first 6 months after prophylactic tooth extractions. The temporary removable dentures affected the patients' ability to chew, swallow and speak, caused pain, and were experienced as an enemy. Despite that, the patients were hopeful and had a wish for recovery, which gave them the energy to live. Conclusion: Prophylactic tooth extractions and temporary removable dentures 6 months after radiotherapy treatment affect head and neck cancer patients' recovery and everyday life. However, they have the will to take on these challenges, pertaining not only to themselves, but also to relatives and health professionals. At the individual level, the patient needs individualized professional support to get through the arduous procedure, from the acute situation until the end of the rehabilitation phase.